Umayyad Relations with Byzantium Empire - Haidari, Mansoor (Journal of History Culture and Art Research, 2017)
This research investigates the political and military relations between Umayyad caliphates with the Byzantine Empire. The aim of this research is to clarify Umayyad caliphate’s relations with the Byzantine Empire. We know that these relations were mostly about war and fight. Because there were always intense conflicts between Muslims and the Byzantine Empire, they had to have an active continuous diplomacy to call truce and settle the disputes. Thus, based on the general policy of the Umayyad caliphs, Christians were severely ignored and segregated within Islamic territories. This segregation of the Christians was highly affected by political relationships. It is worthy of mentioning that Umayyad caliphs brought the governing style of the Sassanid kings and Roman Caesar into the Islamic Caliphate system but they didn’t establish civil institutions and administrative organizations.